The Possibility of Manipulated IPO Underpricing and Post-IPO Stock Return: Empirical Study on Jakarta Stock Exchange 2009-2012 - Purwanto, Sugeng (UI Scholars Hub, 2014)
Ritter and Welch (2002) explain there are two types of IPO firms, namely higher quality firms and lower quality firms. This research propose the third type, namely bad IPO firms which manipulate and force IPO underpricing. Bad IPO firms are subset of lower quality IPO firms that force false signal as higher quality firms. The false signal was hidden by managing post-IPO trading. Trading management are indirectly funded by using balance sheet cash. Hypothesis testing with the empirical model 1 was to confirm the role of CashRatio as the moderating variable that interact DER to affect IPO underpricing which originally was not. The findings support the predictions that interactive variable DER*CashRatio affect IPO underpricing. A managed trading had a non negative profits constraint so that selective post-IPO trading was conducted to cause trading imbalance observable as skewed trading volume (Skewness). Subsequent tests with the empirical model 2 was to confirm the role of Skewness as the moderating variable that interact VolRatio to affect post-IPO stock return (RGM) which originally was not. The findings support the predictions that interactive variable LnVolRatio*Skew affect RGM. Both findings confirm this research predictions on the possibility of manipulated IPO trading in Indonesia IPO 2009-2012.